Morphometric analysis of the abducens nerve in the petroclival region - Bach, M.; Schmeisser, M. J.; Schumann, S. (Frontiers in Surgery, 2025)
BackgroundThe abducens nerve (AN), our sixth cranial nerve, is responsible for the innervation of the lateral rectus muscle of the eye. The abducens nerve is a vulnerable structure at the skull base with its long intracranial course and complex topographic relationships. The AN anatomy in the petroclival region, where the nerve passes from the posterior to the middle cranial fossa, is of great interest for neurosurgical procedures. Despite detailed studies of its anatomy from the past 150 years, there is a need for more recent data on macroscopical and microscopical aspects of the AN in well defined populations.MethodsWe investigated macroscopical variations and the number of nerve fibers of the AN in the petroclival region in German body donors.ResultsIn our histological samples (n = 24) we counted 4688 (+/−1,041) nerve fibers per AN. There was no correlation between sex, age and body side regarding the number of nerve fibers. In our macroscopic examination (n = 76 skull base sides), we found six duplications (four left-sided, two right-sided; 7.9%) and one triplication (right-sided; 1.3%) of the AN in the petroclival region. The AN triplication was further examined: Three nerve bundles pierce the dura mater separately and united before passing under the petrosphenoidal ligament (of Gruber).ConclusionVariations of the AN in the petroclival region are not a rare phenomenon but occur very frequently. Consequently, we have developed a new classification system for AN variations. This knowledge might help neurosurgeons, as it prepares them to be aware of such variations and adapt their surgical approaches accordingly.